2006
DOI: 10.5032/jae.2006.03024
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Learning in the Affective Domain Using Reflective Writing About a Virtual International Agriculture Experience

Abstract: Agricultural educators are familiar with the three domains of learning: 1) cognitive, 2) affective, and 3) psychomotor. When teaching agricultural content, the instructional and assessment strategies are typically focused on the cognitive domain of learning because of the difficulty in measuring gains in the affective domain. The purpose of this study was to measure affective learning after viewing an asynchronously delivered simulation, reflecting (metacognition), and writing about the experience. Research in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 23 publications
1
18
0
2
Order By: Relevance
“…Ultimately, this study demonstrated, albeit at a small-scale localised level, that reflective writing may well be used as an assessment tool for measuring changes in the values, motivations, attitudes and beliefs of students. In comparison with cognitive and behavioural learning, the affective domain is, however, in the words of Boyd, Dooley, and Felton (2006), a … less trodden path in need of further exploration and inquiry.…”
Section: Resultsmentioning
confidence: 95%
“…Ultimately, this study demonstrated, albeit at a small-scale localised level, that reflective writing may well be used as an assessment tool for measuring changes in the values, motivations, attitudes and beliefs of students. In comparison with cognitive and behavioural learning, the affective domain is, however, in the words of Boyd, Dooley, and Felton (2006), a … less trodden path in need of further exploration and inquiry.…”
Section: Resultsmentioning
confidence: 95%
“…Bu yöntem tıp fakültesinde etik eğitimi için "durumun ayrıntıları; ilgili erdemler; ilgili ilkeler, değerler ve etik çerçeve; bir dizi kabul edilebilir davranış yolu" unsurlarını kapsamaktadır. Boyd, Dooley ve Felton (2006) tarım eğitimindeki deneyimlerine ilişkin yazılarından yola çıkarak öğrencilerin duyuşsal kazanımlarını değerlendirmiştir. Çalışma sonuçları bazı öğrencilerin duyuşsal öğrenmenin üst basamaklarına ulaştıklarını ve yansıtıcı yazma becerilerini geliştirdiklerini ortaya koymuştur.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…For example, in this process, the learner gains the confidence, values, and vision to move forward and apply his or her knowledge in action. Similarly, Boyd et al (2006) describe how they see affect leading to action:…”
Section: Learning Domains and Potential Program Outcomesmentioning
confidence: 99%
“…While the process of knowledge and skill acquisition (cognitive and psychomotor domains) is a standard focus for many adult agriculture education programs, less attention is given to developing the affective (attitudes and values) that enable learners to bridge the gap between knowledge and action (Lieblein et al, 2007;Boyd et al, 2006). Drawing from Bloom's (1956) classifications, Geir Lieblein's teaching team created an agroecology program that emphasizes the importance of the affective domain, in addition to the cognitive and psychomotor.…”
Section: Learning Domains and Potential Program Outcomesmentioning
confidence: 99%